Critical reflections on health services development in India : the teleology of disorder - Nayar, K. R., 1955- (Lexington Books, 2014)
This book offers a teleological explanation for the under-development of health services in India by knitting together various actors and subactors within it, while providing rich insights for future research in global public health.